The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00213-003-1486-y
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-onset nicotine self-administration modeled in female rats

Abstract: Adolescent-onset nicotine self-administration in female rats was associated with significantly higher levels of nicotine self-administration versus rats, which began nicotine self-administration in adulthood. This greater self-administration persists into adulthood and may underlie greater propensity of adolescents to nicotine addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
161
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 44 publications
24
161
1
4
Order By: Relevance
“…These present findings with the FR1 and FR2 reinforcement schedules are consistent with the study by Belluzzi et al (2005) in which no age differences for nicotine selfadministration were observed under the FR1 reinforcement schedule. Our results are also partly consistent with the study by Levin et al (2003), in which adolescent and adult female rats earned a similar number of nicotine infusions during the early phase of training, when the younger rats were in late adolescence (P43-46).…”
Section: Nicotine Self-administration In Adolescent and Adult Ratssupporting
confidence: 92%
See 1 more Smart Citation
“…These present findings with the FR1 and FR2 reinforcement schedules are consistent with the study by Belluzzi et al (2005) in which no age differences for nicotine selfadministration were observed under the FR1 reinforcement schedule. Our results are also partly consistent with the study by Levin et al (2003), in which adolescent and adult female rats earned a similar number of nicotine infusions during the early phase of training, when the younger rats were in late adolescence (P43-46).…”
Section: Nicotine Self-administration In Adolescent and Adult Ratssupporting
confidence: 92%
“…Using conditioned place preference (CPP) and conditioned taste avoidance (CTA) procedures, we and others reported that adolescent rats are more sensitive to the rewarding effects of nicotine and less sensitive to its aversive effects than adult rats (Vastola et al, 2002;Belluzzi et al, 2004;Torrella et al, 2004;Wilmouth and Spear, 2004;Shram et al, 2006). Furthermore, several investigators reported that adolescent rats may acquire nicotine self-administration faster than adult rats (Levin et al, 2003;Belluzzi et al, 2005;Chen et al, 2007). However, the degree to which the findings from these self-administration studies reflect increased vulnerability to nicotine's rewarding effects in adolescents is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Without experiencing any negative effects of nicotine to deter smoking behavior, adolescents are more likely to continue smoking. Furthermore, there is a large body of literature demonstrating that adolescent rats are more sensitive to the reinforcing [2,13] and stimulant [8] effects of nicotine. Taken together, it appears that adolescent rats are more sensitive to the positive effects of nicotine reward and less sensitive to the negative effects of nicotine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it seems that smoking behavior is motivated by both the positive reinforcing effects of nicotine and avoidance of the negative effects associated with nicotine withdrawal. Studies using animal models indicate that enhanced reinforcing effects of nicotine may contribute to tobacco use during adolescence [2,8,13,25]. Recent work demonstrates that the physical signs of nicotine withdrawal are lower in adolescent relative to adult rats [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence appears to be a critical period for the initiation of smoking in humans (Eissenberg and Balster, 2000), and the acute effects of nicotine enhance rat locomotor activity in early adolescent rats and suppress it at later ages (Vastola et al, 2002;Faraday et al, 2003;Belluzzi et al, 2004). Early adolescence also appears to be a period of increased sensitivity to the rewarding effects of nicotine (Adriani et al, 2002;Vastola et al, 2002;Belluzzi et al, 2004), and Levin and co-workers have shown that female rats, aged P54, have higher rates of nicotine intake than do older animals (Levin et al, 2003). Thus, we have evaluated the possible synergistic interactions of acetaldehyde and nicotine in a rat self-administration acquisition test in both juvenile and adult rats.…”
Section: Introductionmentioning
confidence: 99%